Risk of severe lower extremity arterial disease in elderly Japanese patients with type 2 diabetes: a propensity score-matched model analysis of sodium-glucose cotransporter 2 inhibitors versus metformin - Takeshi Horii; Yoichi Oikawa; Akira Shimada; Marina Kawaguchi; Yuichi Ikegami; Kiyosi Mihara (BMJ Open Diabetes Research & Care)
Introduction Lower extremity arterial disease (LEAD) represents a significant atherosclerotic complication in patients with type 2 diabetes (T2D). Sodium-glucose cotransporter 2 inhibitors (SGLT2is) and metformin are commonly prescribed glucose-lowering agents that have demonstrated potential benefits in attenuating atherosclerosis progression. This study examined the impact of SGLT2is and metformin on the risk of developing severe LEAD in elderly patients with T2D.Research design and methods This retrospective cohort study analyzed insurance data for individuals aged 65 years and older with advanced-age health insurance coverage, using health insurance claims and self-reported health check-up data. The observation start date was the initial prescription date of SGLT2is or metformin. Severe LEAD was defined as cases requiring revascularization after a LEAD diagnosis. We conducted a 3-year analysis using propensity score matching to compare the distinct effects of each drug on LEAD risk using a claims database.Results The final population comprised 31,732 new SGLT2i and metformin users, divided into two groups (n=15,866 patients each). LEAD incidence rates were 2.10 and 2.69 per 1,000 person-years for metformin and SGLT2is, respectively. Compared with metformin, SGLT2is showed a higher HR for severe LEAD, especially in patients with a diastolic blood pressure (dBP) below 80 mm Hg (HR: 2.11; 95% CI: 1.01 to 2.30) and an estimated glomerular filtration rate between 30 and 60 mL/min/1.73 m2 (HR: 2.32; 95% CI: 1.09 to 2.94).Conclusion The endothelial benefits of metformin, achieved without affecting hemodynamics, may be particularly effective in elderly patients with T2D and low dBP or impaired renal function. However, the presence of cardiovascular disease may often lead to the selection of SGLT2is. Nevertheless, prioritizing the use of metformin may be prudent when considering LEAD status.